Oxytocin Receptor Binding Sites in the Periphery of the Neonatal Prairie Vole - Greenwood, Maria A.; Hammock, Elizabeth A. D. (Frontiers in Neuroscience, 2019)
The oxytocin receptor (OXTR) has been observed in the periphery of neonatal C57BL/6J mice (Mus musculus), including facial regions and the anogenital area. In those studies, ligand specificity was confirmed with a congenital OXTR knockout mouse as well as competitive binding techniques. The aim of this study was to determine if OXTR is present in the same peripheral sites in the neonatal prairie vole (Microtus ochrogaster) for cross-species comparisons. Receptor autoradiography was performed on 20μm sagittal sections of whole postnatal day 0 (P0) male and female prairie voles using the 125iodinated-ornithine vasotocin ([125I]-OVTA) radioligand. A competition binding assay was used to assess the selectivity of [125I]-OVTA for peripheral OXTR. Radioactive ligand (0.05nM [125I]-OVTA) was competed against concentrations of 0 nM and 1000 nM excess unlabeled oxytocin (OXT). Previously identified regions of significant OXTR ligand binding in the mouse were analyzed for comparison: rostral and lateral periodontium, olfactory epithelium, ciliary bodies of the eye, whisker pads, adrenal gland, and anogenital area. We also evaluated the liver and scapular brown adipose tissue, which displayed strong but non-specific signal on film in mice. While there were some areas that showed conserved OXTR ligand binding in the prairie vole (e.g. ciliary body of the eye and the anogenital area), areas showing OXTR ligand binding in the neonatal prairie vole were not identical to OXTR ligand binding in the periphery of the C57BL/6J neonatal mouse. Further, some of the regions measured in the prairie vole suggest sex differences in OXTR ligand binding. Collectively, as is well-established in the central nervous system, these data indicate that patterns of OXTR ligand binding in the infant periphery are species-specific.